Initial experiences of switching to faricimab for neovascular age-related macular degeneration and polypoidal choroidal vasculopathy in an Asian population - Ibrahim, Farah N. I.; Teo, Kelvin Y. C.; Tan, Tien-En; Chan, Hiok Hong; Chandrasekaran, Priya R.; Lee, Shu-Yen; Tan, Anna C. S.; Mathur, Ranjana; Chan, Choi Mun; Sim, Shaun S.; Tan, Gavin Siew Wei; Yeo, Ian Y. S.; et al. (Frontiers in Ophthalmology, 2024)
Purpose To describe the early experiences of patients with neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV) whose treatment was switched to faricimab from other anti-vascular endothelial growth factor (VEGF) agents. Methods This is a prospective cohort of eyes with nAMD and PCV that were previously treated with anti-VEGF agents other than faricimab. We evaluated visual acuity (VA), central subfield thickness (CST), macular volume (MV), pigment epithelial detachment (PED) height, and choroidal thickness (CT) after one administration of faricimab. Where present, fluid was further evaluated according to intraretinal fluid (IRF), subretinal fluid (SRF), or within PED. Results Seventy-one eyes from 71 patients were included (45.07% PCV and 54.93% typical nAMD). The mean [standard deviation (± SD)] VA, CST, and MV improved from 0.50 logMAR (± 0.27 logMAR) to 0.46 logMAR (± 0.27 logMAR) (p = 0.20), 383.35 µm (± 111.24 µm) to 322.46 µm (± 103.89 µm (p < 0.01), and 9.40 mm3 (± 1.52 mm3) to 8.75 mm3 (± 1.17 mm3) (p < 0.01) from switch to post switch visit, respectively. The CT reduced from 167 µm (± 151 µm) to 149 µm (± 113 µm) (p < 0.01). There was also a significant reduction in the maximum PED height between visits [302.66 µm (± 217.97 µm)] and the post switch visit [236.66 µm (± 189.05 µm); p < 0.01]. This difference was greater in PEDs that were predominantly serous in nature. In the eyes with typical nAMD (n = 39), improvements were significant for CST, MV, CT, and PED. In the eyes with PCV (n = 32), only reductions in CT were statistically significant, while VA, CST, MV, and PED only showed numerically smaller improvements. One patient developed mild vitritis without vasculitis, which resolved with topical steroids with no sequelae. Conclusions In our case series of Asian nAMD patients, switching to faricimab was associated with a stable VA and meaningful anatomical improvements, particularly with typical nAMD subtypes.